Legal Consequences of Creditors Recipients of Fiduciaries who are not Registered Judging from Law Number 42 of 1999 concerning Fiduciary Guarantees - Napitupulu, Diana R. W. (Jurnal Smart Hukum (JSH), 2024)
The law of not registering fiduciary creditors has significant consequences for the enforceability and validity of fiduciary guarantees. Based on Law Number 42 of 1999 concerning Fiduciary Guarantees, creditors receiving fiduciaries must be registered as members of the Fiduciary Guarantee Council. Failure to register a fiduciary creditor can give rise to legal problems in terms of executing fiduciary guarantees, because the guarantee cannot be used as evidence or a legal resource. Therefore, efforts need to be made to prevent this from happening and ensure that creditors who receive fiduciaries meet the requirements to be registered as members of the Fiduciary Guarantee Council. This research uses a qualitative data analysis approach to conduct normative legal studies. The main legal sources in this research are primary legal sources. The conclusion of this research is that an unregistered fiduciary agreement has legal consequences, where the creditor does not have a preferred position in the event of bankruptcy and only acts as a concurrent creditor. And if the debtor defaults, the creditor does not have direct executorial rights over the fiduciary collateral, if the debtor is unable to pay off the entire debt at the agreed time.